Influence of Ion Current on Current Transformes of AC Systems in Near Vicinity of DC Systems - Romeis, Christian; Jäger, Johann, Kristian Steckler; Keil, Timo (2015 IEEE Eindhoven PowerTech, 2015)
Equipping one support structure with DC and AC systems in parallel can increase the transport capacity of existing transmission corridors. The constant electric field of the DC system induces a constant DC component into the AC systems in near vicinity. All magnetic equipment including an iron core is in danger to saturate. Especially current transformers (CTs) for protection issues can be influenced in the way that the time-to-saturation is reduced. Therefore, maybe the protection relays are affected adversely and the selectivity is harmed. This paper evaluates this major impact by determining the transient dimensioning factor and the time-to-saturation in presence of a constant DC component in the fault current and remanent flux. The influence on the transient dimensioning factor is marginal and can be almost neglected. But for metering cores it could be a problem and should be tested because of the different excitation curve